Dinamismo histórico de la fauna brasílica en la Argentina - Ringuelet, Raúl Adolfo (1978)
The historical rangue of the Brazilian fauna in Argentina. - Actually the fauna of the Brazilian Sub Region reaehes to Ventania, south of the Buenos Aires Provinee, and Bahía Blanca. We comment historical facts, from naturalists, expeditionaires and travellers in the XVII and XIX centuríes about anímals of tropical character and now disappeared. The geographical distributíon in other countries reveals the presence of a Guayano-Brazilian fauna entirelly isolated, for instance, the Opiliones of Patagonian Cordillera and South Chile, the Palpatores of Tarapaca, northern Chile, the Characinids Cheirodon in the same region, the "Naked Characinid" in the basaltic area of Somuncará in north Patagonia, the transandean freshwater leeches Crustaceans and Fishes of Ecuador and northern Peru. The comparison of marine and terrestrial fauna from late Tertiary by Simpson's index of similitude, confirmed the paulatine retraction of the tropical fauna of Brazilian Genocenter in the south Pampasic dominion and Patagonia, phenomen initiated in the mid Tertiary. Actually, the plains of meridional Pampasic Dominion are a gigantic ecotone with increased penetration of Patagonian and Subandine fauna.